1989
DOI: 10.1002/bdd.2510100108
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of propranolol hydrochloride tablet formulations: Application of multiple dose crossover studies

Abstract: Two multiple dose crossover pharmacokinetic studies were carried out to determine the steady-state bioavailability of newly formulated generic propranolol HCl tablets relative to Inderal tablets. In Study I, 24 healthy volunteers were dosed with 4 x 10 mg test tablets, 1 x 40 mg test tablet, 4 x 10 mg Inderal tablets, and 40 mg of propranolol HCl in solution. In Study II, 24 healthy volunteers were dosed with 1 x 80 mg test tablet, 1 x 80 mg Inderal tablet, and 80 mg of propranolol HCl in solution. Both studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Interestingly, our group has previously shown in the same forehead model that the trigeminal nerve‐induced vasodilatory responses and hormone levels are altered in female migraine patients. 19 Moreover, a recent study in rodents showed that application of CGRP to the cranial meninges results in behavioral responses consistent with headache in preclinical models in a female‐specific manner, 48 reinforcing the interaction between sex hormones and CGRPergic fibers in the modulation of the trigeminovascular system. 20 Additionally, sexually dimorphic responses to propranolol have also been reported in a murine model of addiction, where in males the mechanism of action of propranolol involved 5‐HT signaling, whereas in females it involved both β‐adrenergic and 5‐HT signaling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, our group has previously shown in the same forehead model that the trigeminal nerve‐induced vasodilatory responses and hormone levels are altered in female migraine patients. 19 Moreover, a recent study in rodents showed that application of CGRP to the cranial meninges results in behavioral responses consistent with headache in preclinical models in a female‐specific manner, 48 reinforcing the interaction between sex hormones and CGRPergic fibers in the modulation of the trigeminovascular system. 20 Additionally, sexually dimorphic responses to propranolol have also been reported in a murine model of addiction, where in males the mechanism of action of propranolol involved 5‐HT signaling, whereas in females it involved both β‐adrenergic and 5‐HT signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Before each measurement, a standardized light meal was provided. Measurements were performed before and 90 min after either placebo or propranolol (corresponding to the time to propranolol peak plasma concentration 19 , 20 ) during the two research visits. During the experiment, the subjects rested supine on a bed and were not allowed to speak.…”
Section: Methodsmentioning
confidence: 99%
“…This may be partly due to differences in bioavailability between the two brands. Studies have demonstrated that drugs known to be legally chemically equivalent are not at the same time clinically equivalent 6,7,8,9…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provide evidence that various non-therapeutic brand-name and generic drugs that are pharmaceutical equivalent produce different therapeutic effects 6,7,8,9,10. Approximately 20% of primary care patients experience chronic pain, and pain screening is intended to improve the quality of pain management by systematically identifying patients with pain in clinical settings, but currently there is no commonly accepted gold standard for clinically important pain 11.…”
Section: Introductionmentioning
confidence: 99%
“…Propranolol hydrochloride extended release capsules (Par Pharmaceuticals) were used, because this formulation has been rated by the FDA as bioequivalent to Inderal LA. 23 …”
Section: Methodsmentioning
confidence: 99%